A Statistical analysis on Lamoiyan Corporation - Cordova, Kenneth Irving (College of Engineering, 2002)
Lamoiyan Corporation has been known as the makers of Hapee Toothpaste and Dazz dishwashing paste. The toothpaste production comprises 57 percent of the total production of the company. With that, the study will be focusing on its primary product line. Having done the problem analysis, it was shown that high percent yield of rejects has been present in the system. The allowable percentage is 0.05 percent of the total production. But based on the records, the values ranges from 0.06 percent to 0.15 percent, which are higher than the set allowable. This was due to the improper sealing of the toothpaste tubes, inappropriate amount of filled toothpaste in tubes and defective toothpaste tubes. Improper sealing was found to be greatly affected by three factors. These are operator of the filling machine, temperature necessary for sealing and the thickness of the toothpaste tubes. The design for the experiment is 2 factorial design. The response variable is the angle of inclination of the seal in the tubes. A Goodness of Fit test was used to determine if the data follows a normal distribution. Having done this, it was found that the data follows a normal distribution. The statistical analysis for the design was performed using different tools. Using ANOVA, the factors that the design was performed using different tools. Using ANOVA, the factors that affect the sealing process are the thickness of the tubes and the temperature used in sealing. Also, a regression model was formed for easy interpretation of the performed analysis. The model is Y = 4.1 - X2 - 1.55X3 + 0.75X2X3 - 0.65X1X2X3. Normal Probability and Residual plots were also used to further analyze the data. Using the Graphical Analysis, the temperature must be maintained at 310 degree celcius and the thickness at 280 mm. For the second problem, which is inappropriate amount of filled toothpaste in tubes, Two Factorial Design was used. The two factors are the operators and the amount of pressure in the filling tubes. Having done the Analysis of Variance, it was found that the amount of pressure affects the filling process. Duncan's Multiple range test was also performed which showed that all the levels were significantly different. Also, through graphical analysis, the pressure must be maintained at the standard level of 70mmHg. From the analyses performed, the group recommends level of temperature during the sealing process and the pressure for filling process must be maintained at the standard level to properly control the operations and minimize rejects. Since the thickness also affects the sealing process, it must be set at a standard size also for the same reasons. Last problem would be left as area for further study.